The prodigal church : a gentle manifesto against the status quo - Wilson, Jared C., 1975- (Wheaton, Illinois : Crossway, 2015)
This book is not a tired rant. This book is not a reactionary diatribe. This book is a gentle manifesto against the status quo.In The Prodigal Church, Jared Wilson challenges church leaders to reconsider their priorities when it comes to how they "do church" and reach people in their communities, arguing that we too often rely on loud music, flashy lights, and skinny jeans to get people in the door.Writing with the grace and kindness of a trusted friend, Wilson encourages readers to reexamine the Bible's teaching, not simply return to a traditional model for tradition's sake. He then sets forth an alternative to both the attractional and the traditional models: an explicitly biblical approach that is gospel focused, grace based, and fruit oriented. - back of book
The parable of the prodigal church -- What this book is not -- What if the system's broken? -- What works? -- The Bible is not an instruction manual -- From watching to beholding -- Biting off more than you can chew -- Pastoring hearts -- A way forward -- The prodigal church comes home -- A portrait of the author as a young man -- A call to the gospel renaissance.
Includes bibliographical references and indexes.
Keywords: Church; Prodigal Church